Multiple Challenges: An Unusual Case of an Adrenal Mass With Plurihormonal Secretion of Catecholamines and Cortisol in a Patient With Several Neoplasms - Anna Elvira Seelin Arcellana; Franz Magnaye; Carmegie Caparida Saliba; Soriano Capaya; Jonathan Rivera; Denorson Sotalbo; Emmeline Elaine Cua; Inah Jane Coronel; Ralph Jason Li (Journal of the Endocrine Society, 2021)
Abstract Introduction: Simultaneous hypersecretion of both catecholamines and cortisol in one adrenal tumor is rarely seen because cortical cells, which produce cortisol, and medullary cells, which secrete catecholamines, are derived from different germ layers1. Formidable challenges ensue from a tumor with a complex behavior. We demonstrate here the clinical course and multi-modal management of the case of an adrenocortical adenoma which had neuroendocrine differentiation accounting for the excess of both catecholamine and cortisol hormones in a patient with multiple neoplasms. Clinical Case: An adrenal mass was incidentally discovered in a 61-year old female undergoing imaging as part of the metastatic work-up for an esophageal mass. The patient has insulin-requiring diabetes mellitus, hypertension and a history of breast cancer. A right adrenal gland mass, avidly enhancing, measuring 3.8 x 2.7 x 2.7 cm was found on abdominal imaging. The 24-hour urine metanephrine collections were done, and these were more than twice elevated in two instances at 2.516 mg/24 hours and 2.101 mg/24 hours (NV: 0–1 mg/24 hours). An unsuppressed cortisol level at 6.57 μg/dL (NV: ≤ 1.8 μg/dL) was obtained after the 1 mg dexamethasone suppression test. Hypercortisolism was confirmed with an elevated 24-hour urine free cortisol at 312.07 μg/24 hours (NV: 20–90 μg/24 hours). Adrenocorticotrophic hormone (ACTH) was low at 0.90 pg/ml, indicative of the presence of an adrenal form of Cushing’s. Primary aldosteronism was ruled out based on a ratio between plasma aldosterone concentration and plasma renin activity of less than 20. Pre-operative alpha blockade with terazosin was initiated. Right adrenalectomy was done. Histopathology revealed an adrenal mass of cortical origin, atypically staining positively for synaptophysin, which is indicative of neuroendocrine differentiation of the tumor. The patient had better blood pressure and glycemic control after the adrenalectomy. Clinical Lessons: An adrenocortical adenoma very seldom undergoes neuroendocrine differentiation. Pathophysiologic mechanisms include a genetic aberration in cortical cells leading to production of catecholamines2. This case underscores the importance of a comprehensive biochemical evaluation of a patient with an adrenal mass because control of hormonal hypersecretion is essential in reducing cardiovascular risks, morbidity and mortality. References: 1Duan L, Fang F, Fu W, et al. Corticomedullary mixed tumor resembling a small adrenal gland-involvement of cancer stem cells: case report. BMC Endocr Disord. 2017;17(1):9. Published 2017 Feb 13. doi:10.1186/s12902-017-0157-7.2Donatini G, Van Slycke S, Aubert S, Carnaille B. Corticomedullary mixed tumor of the adrenal gland-a clinical and pathological chameleon: case report and review of literature. Updates Surg. 2013 Jun;65(2):161–4. Epub 2012 Jan 7. PMID: 22228558.